Significance of ARID1A in neuroblastoma onset mechanism - Jin, Duo; Zhang, Dong; Tang, Qinyu (Frontiers in Oncology, 2025)
Neuroblastoma (NB) is a prevalent pediatric malignancy with poor clinical outcomes. As one of the most common childhood malignancies, it can arise in various locations along the sympathetic nervous system, complicating both fundamental studies and therapeutic approaches. The ARID1A protein has emerged as a pivotal regulator in the pathogenesis of diverse tumor types within oncology research. Recent studies have increasingly focused on the functional role of ARID1A in NB pathogenesis. As a tumor suppressor, ARID1A loss-of-function mutations enhance migratory and invasive capacities of NB cells through cell cycle dysregulation, thereby promoting tumor cell proliferation. At the molecular level, ARID1A functions as the core subunit of the BAF chromatin remodeling complex, critically regulating the proliferative behavior of tumor cells. Although research in this field remains at an early stage, it has established a solid foundation for elucidating NB pathogenesis, with promising implications for improving clinical outcomes and quality of life in affected children. This review summarizes the critical role of ARID1A in NB and explores emerging therapeutic strategies, with particular emphasis on targeted protein degradation approaches and immunotherapeutic interventions.